PENDIDIKAN DAN ILMU PENGETAHUAN PERSPEKTIF AYAT AL-QUR’AN - Farkha Maulida; Azkya Putri Mukhayati (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2023)
Abstract Education and science are an inseparable unity. In the educational process, of course, there is knowledge that can be obtained and in obtaining knowledge, of course, there are educational activities that must be done. People need education to gain knowledge as a provision for life and obtain truth. Education and science in Islam are seen as part of man's obligation as a creation of God who has reason and mind. Islam as a religion that prevails throughout the ages is very open to the existence of science and encourages progress. In order to understand Islamic education and knowledge should examine the verses of the Qur'an that talk about education and science. Education and science in Islam are seen as part of man's obligation as a creation of God who has reason and mind. Islam as a religion that prevails throughout the ages is very open to the existence of science and encourages progress. In order to understand Islamic education and knowledge should examine the verses of the Qur'an that talk about education and science. The method of writing this article is by collecting verses of the Qur'an related to education and science